La Inmigración de posguerra en la Argentina: identidad individual, identidad familiar y fuentes epistolares - María Liliana Da Orden (IdeAs)
The article explores the ways of creation and recreation of individual and family identity with the aim of proposing some directions that advance the study of adaptation of postwar immigrants in Argentina. The main source is the correspondence of a member of an Italian family from Sicily who settled in Buenos Aires in the late forties. It is a collection of more than a hundred letters, most of which were written by a native of Valguarnera (province of Enna) who emigrated as a child with his family and in the sixties left for the United States, leaving some of his relatives in the Argentinian capital. In the first part we consider the characteristics this family shared with the wave of Sicilians entering the country, in the context of the postwar migration flow to Argentina. In the second part, focusing on correspondence, I suggest that despite the successive migrations and the process of social mobility experienced, the "extended" family continued to have a central place in the lives of these immigrants. But at the same time, the letters became the instrument of a process of adaptation where the kin was losing some of its power. Thus, the continuity of the correspondence resulted in a double play where individual autonomy stepped ahead of family interests without entirely displacing them.